O efeito dos tratamentos de nitretação por plasma e têmpera superficial a laser nas propriedades superficiais de ferros fundidos vermiculares - Writzl, Viviane (2018)
In search of greater efficiency, the development of new engines has increased to the mechanical and thermal demands of the components. The specific properties of Compacted Graphite Iron (CGI), such as wear resistance, higher strength to weight ratio and its economic and technological advantages compared to other cast iron, make it an excellent choice for applications in diesel engine blocks and others. The combined application of two or more surface treatments emerged as an alternative to improve the performance of components to increase the resistance to contact fatigue and abrasion, decrease the friction coefficient, and thermally insulate the surface, among other. In this work the influence of the nitriding time on plasma and the power of surface laser hardening on the surface properties of Compacted Graphite Iron (CGI) were studied. The laser hardening treatment in nitrided cast iron allowed for high surface hardness, higher hardening depths due to the formation of martensite, and mainly a reduction of the hardness gradient between the nitrided layer and the substrate by solubilization of the nitrides and diffusion of the nitrogen to the interior of the part. The analysis of phases by x-ray diffractometry in the nitrided samples followed by laser hardening allowed to identify, for all the laser power conditions, a reduction of the intensity of the peaks corresponding to the nitrides ε and ’ phases present on the surface, as well such as the presence of peaks corresponding to the α’ phase (martensite), retained austenite and Fe2O3 (oxides). It was also verified the decomposition of the nitrites and the appearance of the FeN0,076 phase in higher powers of the laser. Scratch tests with progressive loading showed better tribological performance after surface laser hardening treatment in nitrided CGI, when compared to these treatments alone or without treatment. The modified layer provided greater mechanical support under critical wear loads by reducing the hardness gradient between the treated layer and the substrate, as well as a reduction of the brittleness of the nitrided layer contributed to lower coefficients of friction.